Zakat in Employees Income Tax - Titin Ruliana (LPPM University 17 Agustus 1945 Samarinda, 2017)
The income tax is one of the most frequent tax levied by the government and pay taxes is an obligation for the people of Indonesia. In addition, in the Islamic religion is also the obligation to pay zakat profession for those who have fulfilled the nisab to pay zakat. The government has issued regulation PP. 60 of 2010 concerning Zakat or compulsory religious contribution that may be deducted from gross income referring to Law No.38 of 1999 and then renewed to become law No.23 of 2011 on the management of zakat. This is done so as not to double load. This research is conducted on shipping company is to calculate and analyze the appropriateness of zakat application as deduction of income tax of employee (PPh 21) with zakat management law. 23 of 2011.Research coverage on the application of professional zakat (Zakat Law No.23 of 2011 on Zakat Management) as a deduction of income tax of employees (Tax Law No. 36 of 2008). The research was conducted at Sailing Company in Samarinda, East Kalimantan Province. This study uses employee payroll data in 2015. This study uses the following analytical tools: (1) The tax rate stipulated on the taxable income of the individual taxpayer in the country, as set forth in article 17 paragraph 1 of Law No.36 of 2008; (2) Non-Taxable Income (PTKP) Article 7 paragraph 1 Law No.36 of Law No.36 of Year 2008; 3) Income Tax (PPh) Article 21 of Law No.36 Year 2008; (4) of Law no. 23 Year 2011 About Management of Zakat Chapter IV Article 11 on Calculation of Nisab and Haul Zakat.